Contingency learning of social cues: neural engagement and emotional modulation by facial expressions - Saylik, Rahmi; Uysal, Burcu; Williams, Adrian Loyd; Murphy, Robin A. (Frontiers in Human Neuroscience, 2025)
Contingency learning—the fundamental process by which associations are formed between events in our experience is as relevant of conditioning as it is for social interactions, where emotional cues, such as facial expressions, signal complex and reciprocal causal dynamics. This study investigates the functional neuroanatomy underlying contingency perception by with three type of contingent relation (positive, zero, and negative) using sad and happy facial expressions as stimuli in a group of neurotypical participants. Employing a streaming trial paradigm and functional MRI, we examined how these emotional contingencies engage brain regions involved in attention and predictive processing. The behavioural results indicated that participants could distinguish between different contingencies, regardless of the emotional stimuli. However, judgment ratings varied across conditions, with sad expressions eliciting weaker ratings compared to happy expressions, which moderated perceived causality, especially in the uncorrelated and negative contingency tasks. These behavioural findings were primarily linked to increased activation in frontal regions, including the inferior frontal gyrus, middle frontal gyrus, and anterior cingulate cortex. The results highlight the differential cognitive demands and neural responses evoked by emotional expressions and suggestive of the idea that statistical relations that violate social expectations are processed differently than positive relations.